Through the Eyes of Healthcare Providers, the Necessity and Challenges of Implementing Medication Reconciliation at Hospital Discharge: A Qualitative Study - Ali, Melad Mohammed; Al-Jumaili, Ali Azeez (AL-Kindy College Medical Journal, 2024)
Background: Medication reconciliation can include medication reviewing and providing counseling and a list of all the medications during every transition of care.Objectives: to explore in-depth the perspectives of Iraqi physicians and pharmacists regarding the necessity of medication reconciliation at hospital discharge and identify the possible benefits and challenges that could face its implementation.Subjects and Methods: A qualitative study included semi-structured interviews with pharmacists and physicians working at a public teaching hospital in Iraq. The interviews were conducted face-to-face from February to March 2023. Thematic analysis was used to analyze the qualitative data generated from the interviews.Results: In this study, 18 healthcare providers were recruited: 12 pharmacists and six physicians. All participants supported medication reconciliation adoption at hospital discharge. Pharmacists can identify unintended medications discrepancies via discharge medication reviewing, patient counseling and providing discharge list. The most frequently reported challenges to establishing medication reconciliation were a lack of clear official instructions, suboptimal physician-pharmacist cooperation, and inadequate awareness.Conclusions: The implantation of medication reconciliation has numerous benefits in terms of enhancing patient safety and avoiding medication errors. However, it needs several pre-requisites to be implemented routinely, including official enforcement and training courses to raise healthcare providers’ awareness.